(untitled) (Praxis Educativa, 2025)
An exploratory and mixed study was carried out in Misión San Patricio (Salta) to describe the cognitive-linguistic abilities, through surveys and interviews, of non-native and native (wichís) secondary school students. They positively identified narrative and expository texts, except for argumentative texts, where they recognised the main idea. In activities of low complexity, a better performance was observed in the narrative genre, and in those of higher complexity, performance was low. The Oriented Cycle students adequately identified the textual superstructures and main idea (only in the expository text) in comparison with those in the Basic Cycle. In the interviews, they stated that they found it better to work with narrative texts, and even more so if they are bilingual. Reading is summarised in locution and diction of the texts, being practised at school only in almost all cases. This could be due to educational, linguistic, economic and cultural factors.